PENGEMBANGAN KARIR SECARA INDIVIDUAL DALAM RANGKA MENCAPAI KEBERHASILAN KARIR: (Studi pada Tenaga Kependidikan Fakultas Ilmu Administrasi Universitas Brawijaya) - Riris Mahmudah Utami; Bambang Santoso Haryono; Lely Indah Mindarti (Jurusan Administrasi Publik, Fakultas Ilmu Administrasi, Universitas Brawijaya, 2022)
This study aims to analyze individual career development based on directed values and self-directed values to achieve objective and subjective career success in education staff at the Facultyi of Administrative Sciences, Universitas Brawijaya. This type of research is a descriptive qualitative approach. Data were collected through observation and interviews and then the data were analyzed using the Miles and Huberman (1992) interactive model. The results of the research show that career development is directed by values about the ability to manage and the ability to direct themselves as a proactive action to develop their career. Value-driven and internal principles that motivate and guide him in his career. Objective career success (material) is considered positive, because they feel that their income is in line with expectations to meet their needs and promotions or job rotations are considered positive because they get additional positions or assignments objectively based on ability and performance. Subjective (psychological) career success was assessed positively, because they were satisfied with the balance of personal and work life.